Compensation, Competence, Organizational Commitment and Its Effect on Employee Performance: Job Satisfaction as Interverning - Milwan Akbar Gunawan; Hendra Gunawan (Pusat P2M Politeknik Negeri Batam, 2019)
This study aims investigate the influence of job satisfaction, compensation, performance on employee performance. How the effect of competence on job satisfaction and how the compensation effect on job satisfaction. Respondents in this study were 180 employees who have high levels of management level low, middle and top management in the telecommunications services company. Research analysis techniques using SEM analysis. The study found that the competence of positive and significant impact directly on job satisfaction; competence significant impact on the performance of employees through job satisfaction; compensation positive and significant effect on employee performance; compensation positive and significant effect on employee performance with going through job satisfaction; job satisfaction significant positive effect on employee performance; organizational commitment insignificant impact on the performance of the employees.